Mathematics teachers' perceptions of the value of geogebra integration in South African high schools - Mokotjo, Lindiwe; Mokhele-Makgalwa, Matseliso (African Perspectives of Research in Teaching & Learning, 2021)
The South African Government has made concerted efforts to introduce GeoGebra and similar open-source dynamic graphics mathematics software to schools. This study appreciates that teachers are crucial in the integration 3of technology that assists in teaching, including GeoGebra, and hence focuses on exploring teachers’ perceptions about the value of using GeoGebra. This article presents four qualitative case studies that illustrate the views and experiences of selected teachers in the integration of GeoGebra within a South African curriculum context. Located in the interpretivism paradigm, the researchers listened to the views, opinions and understandings of teachers concerning the integration of GeoGebra. Data were generated by conducting semi-structured interviews with four purposively sampled teachers from four high schools in the Bojanala District in the North-West Province of South Africa. The key finding of this study revealed the need to strengthen the professional development of teachers concerning the integration of GeoGebra into the mathematics curriculum. The study concluded that teachers are enthusiastic in applying GeoGebra as they believed that it was valuable in teaching mathematics to South African high school student. The study recommends the enhancement of professional development with a focus on GeoGebra because of its strong link to the South African curriculum. Keywords: Information, communication, technology, integration, GeoGebra software, mathematics
Article published in the African Perspectives of Research in Teaching & Learning (APORTAL) 5(1): 2021
Keywords: Information; Communication; Technology; Integration; GeoGebra software; Mathematics; Computer graphics - Mathematics